Analisis Faktor-Faktor yang Mempengaruhi Net Interest Margin Pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016 - Deny Asna Widyanto; R. Ery Wibowo Agung; Alwiyah Alwiyah (Universitas Muhammadiyah Semarang, 2020)
This study aims to examine the effect of liquidity, capital, efficiency, bank size and Non Performing Loans (NPL) on Net Interest Margin (NIM). The population in this study were all banking companies (commercial banks) listed (Go Public) on the Indonesia Stock Exchange (BEI) for the period 2012-2016, totaling 33 banks. The method of taking by judgment sampling method, which is one form of purposive sampling. The data used are secondary data with data analysis using linear regression analysis. Based on the research results, it was found that LDR had a positive and significant effect on NIM. EA has no significant effect on NIM. BOPO has no significant effect on NIM. Bank size has no significant effect on NIM. NPL has a significant effect on NIM. Liquidity, Efficiency Capital, Company Size and Non-Performing Loans have a significant effect on Net Interest Margin (NIM) together.